Arsenic trioxide in pediatric cancer – a case series and review of literature. (12th July 2021) - Abele, Michael; Müller, Sara-Lena; Schleicher, Sabine; Hartmann, Ulrike; Döring, Michaela; Queudeville, Manon; Lang, Peter; Handgretinger, Rupert; Ebinger, Martin
Abstract: Arsenic trioxide (ATO) has become an established component of treatment protocols for acute promyelocytic leukemia (APL) with excellent efficacy and no relevant sustained toxicity. Part of its action has been attributed to the inhibition of Hedgehog signaling (Hh) which enables a possible therapeutic approach as many pediatric tumor entities have been associated with increased Hh activity. We retrospectively analyzed 31 patients with refractory and relapsed pediatric cancer who were treated with ATO at the University Children's Hospital of Tuebingen. Additionally a literature review on the clinical and preclinical use of ATO in pediatric cancer treatment was performed. ATO alone as well as combinations with other drugs have proven effective in vitro and in mouse models of various pediatric malignancies. However, only few data on the clinical use of ATO in pediatric patients besides APL exist. In our patient sample, ATO was overall well tolerated in the treatment of various pediatric cancers, even in combination with other cytostatic drugs. Due to distinct tumor entities, differently progressed disease stages and varying co-medication, no clear statement can be made regarding the efficacy of ATO treatment. However, patients with proven Hh activation in molecular tumor profiling surpassed all other patients, who received ATO in an experimental treatment setting, in terms of survival. As molecular profiling of tumors increases and enhanced Hh activity can be detected at an early stage, ATO might expand its clinical use to other pediatric malignancies beyond APL depending on further clinical studies.